Pan-histone demethylase inhibitors simultaneously targeting Jumonji C and lysine-specific demethylases display high anticancer activities. - Rotili, D; Tomassi, S; Conte, M; Benedetti, R; Tortorici, M; Ciossani, G; Valente, S; Marrocco, B; Labella, D; Novellino, E; Mattevi, A; Altucci, L; et al. (2014)
In prostate cancer, two different types of histone lysine demethylases (KDM), LSD1/KDM1 and JMJD2/KDM4, are coexpressed and colocalize with the androgen receptor. We designed and synthesized hybrid LSD1/JmjC or "pan-KDM" inhibitors 1-6 by coupling the skeleton of tranylcypromine 7, a known LSD1 inhibitor, with 4-carboxy-4'-carbomethoxy-2,2'-bipyridine 8 or 5-carboxy-8-hydroxyquinoline 9, two 2-oxoglutarate competitive templates developed for JmjC inhibition. Hybrid compounds 1-6 are able to simultaneously target both KDM families and have been validated as potential antitumor agents in cells. Among them, 2 and 3 increase H3K4 and H3K9 methylation levels in cells and cause growth arrest and substantial apoptosis in LNCaP prostate and HCT116 colon cancer cells. When tested in noncancer mesenchymal progenitor (MePR) cells, 2 and 3 induced little and no apoptosis, respectively, thus showing cancer-selective inhibiting action.